2017
DOI: 10.1530/eje-16-0815
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of obstructive sleep apnea in patients with Cushing’s syndrome compared with weight- and age-matched controls

Abstract: The prevalence of OSA increased in patients with CS compared with control subjects with similar ages and BMI levels. Hypercortisolemia is an independent risk factor for developing OSA. The presence of OSA needs to be considered in patients with CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Proposed explanations have included elevated growth hormone and insulin‐like growth factor‐I levels that dysregulate the central respiratory drive, and anatomical changes such as increased mandibular and maxillary growth, tongue hypertrophy, and greater oropharyngeal soft‐tissue thickening . The prevalence of OSA is also increased in Cushing's syndrome patients, with hypercortisolemia being an independent risk factor for developing OSA . Obesity, DM, and increased adipose tissue in the subcutaneous tissues of the neck have been attributed to developing OSA in Cushing's syndrome patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed explanations have included elevated growth hormone and insulin‐like growth factor‐I levels that dysregulate the central respiratory drive, and anatomical changes such as increased mandibular and maxillary growth, tongue hypertrophy, and greater oropharyngeal soft‐tissue thickening . The prevalence of OSA is also increased in Cushing's syndrome patients, with hypercortisolemia being an independent risk factor for developing OSA . Obesity, DM, and increased adipose tissue in the subcutaneous tissues of the neck have been attributed to developing OSA in Cushing's syndrome patients …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OSA is also increased in Cushing's syndrome patients, with hypercortisolemia being an independent risk factor for developing OSA . Obesity, DM, and increased adipose tissue in the subcutaneous tissues of the neck have been attributed to developing OSA in Cushing's syndrome patients …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OSA (based on PSG) was higher in women with active CS (n = 35) compared to age-, gender-and BMI-matched controls (n = 30) (50% vs 23%, P = 0.003) (218). After controlling for BMI and HOMA score, serum cortisol remained independently associated with AHI (R 2 : 77.8%, P < 0.001), suggesting that the relationship between CS and OSA are not only related to obesity (218). A recent Taiwanese population-based cohort study showed that patients with CS (n = 53) were at increased risk of developing OSA compared to matched controlled (matched for age, sex and comorbidities including obesity, T2D and hypertension) (4.11 vs 1.70 per thousand person/year; HR 2.82, 95% CI: 1.67-4.77), with slightly higher risk in men vs women (219).…”
Section: Osa In Patients With Cushing's Syndromementioning
confidence: 89%
“…Several studies have shown that OSA is common in patients with Cushing's syndrome (CS) (whether endogenous or exogenous) (217). The prevalence of OSA (based on PSG) was higher in women with active CS (n = 35) compared to age-, gender-and BMI-matched controls (n = 30) (50% vs 23%, P = 0.003) (218). After controlling for BMI and HOMA score, serum cortisol remained independently associated with AHI (R 2 : 77.8%, P < 0.001), suggesting that the relationship between CS and OSA are not only related to obesity (218).…”
Section: Osa In Patients With Cushing's Syndromementioning
confidence: 99%
“…In the first study on obstructive sleep apnoea in patients with active CS, Shipley et al found a prevalence of 32% (seven of 22 subjects), of whom four had clinically significant disorder [61]. More recently, by using overnight polysomnography, Gokosmanoglu et al found the prevalence of obstructive sleep apnoea in a small group of young female patients with newly diagnosed CS to be 50%, compared with 23% in matched controls [64]. In that study, serum cortisol concentrations were independently associated with Apnoea–Hypopnoea Index, after controlling for BMI [64].…”
Section: Neuroimagingmentioning
confidence: 99%